Model Checking Software 19th International Workshop, SPIN 2012, Oxford, UK, July 23-24, 2012. Proceedings - Donaldson, Alastair; Parker, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed proceedings of the 19th International SPIN workshop on Model Checking Software, SPIN 2012, held in Oxford, UK, in July 2012. The 11 revised full papers presented together with 5 tool papers and 4 invited talks were carefully reviewed and selected from 30 submissions. The papers are grouped in topical sections on model checking techniques; parallel model checking; case studies; model checking for concurrency; and tool demonstrations.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs